2000
DOI: 10.1016/s0960-9822(00)00759-4
|View full text |Cite
|
Sign up to set email alerts
|

An empirical genetic assessment of the severity of the northern elephant seal population bottleneck

Abstract: A bottleneck in population size of a species is often correlated with a sharp reduction in genetic variation. The northern elephant seal (Mirounga angustirostris) has undergone at least one extreme bottleneck, having rebounded from 20-100 individuals a century ago to over 175,000 individuals today. The relative lack of molecular-genetic variation in contemporary populations has been documented, but the extent of variation before the late 19th century remains unknown. We have determined the nucleotide sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 12 publications
6
83
0
1
Order By: Relevance
“…48 Furthermore, the nucleotide diversity of the LB population was even lower than that of the bottlenecked Northern elephant seal population (p=0.0065-0.0086). 49 However, BSPs investigating effective population size (N e ) over time did not detect any past bottleneck event (Supplementary Figure 1), a result similar to that obtained in the mismatch distribution analyses (data not shown). Hence, it seems that the recent reduction of the LB population size caused by human activities has not yet caused a severe bottleneck influencing the diversity indices, but rather that older and possibly recurrent events had a more profound effect on the population, as observed by mtDNA sequences.…”
Section: Discussionsupporting
confidence: 80%
“…48 Furthermore, the nucleotide diversity of the LB population was even lower than that of the bottlenecked Northern elephant seal population (p=0.0065-0.0086). 49 However, BSPs investigating effective population size (N e ) over time did not detect any past bottleneck event (Supplementary Figure 1), a result similar to that obtained in the mismatch distribution analyses (data not shown). Hence, it seems that the recent reduction of the LB population size caused by human activities has not yet caused a severe bottleneck influencing the diversity indices, but rather that older and possibly recurrent events had a more profound effect on the population, as observed by mtDNA sequences.…”
Section: Discussionsupporting
confidence: 80%
“…Loss of genetic variation from genetic drift during population bottlenecks has been demonstrated for many species (Weber et al 2000;Vila et al 2003;Goossens et al 2006), as a result of processes such as founder events and isolation after postglacial colonisation (Hewitt 2000; Communicated by P. Alves…”
Section: Introductionmentioning
confidence: 99%
“…To date, relatively few studies of wild populations have examined the loss of genetic variation over the course of a population decline or recovery. In some populations there has been a significant loss of both genetic variation and fitness (Westemeier et al 1998), but in other cases the results are less clear, as the genetic changes have been relatively small (Miller and Waits 2003), the loss of genetic variation predated the population decline (Mundy et al 1997;Pertoldi et al 2001) or the loss of genetic variation was associated with relatively minor effects on fitness (Weber et al 2000;Groombridge et al 2000, Bellinger et al 2003. To date, only two studies of populations in the wild have demonstrated a positive association between genetic variation and the risk of population extinction (Newman and Pilson 1997;Saccheri et al 1998).…”
Section: Introductionmentioning
confidence: 99%